2006
DOI: 10.1681/asn.2006030204
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Talk between the Kidney and the Cardiovascular System

Abstract: In recent years, increasing evidence has been provided that even minor renal dysfunction is a powerful cardiovascular risk factor that induces typical cardiovascular alterations and thus predisposes to coronary heart disease as well as to noncoronary cardiovascular problems. This first had been noted in patients with diabetes but now has been confirmed amply in patients without diabetes as well. Numerous heterogeneous abnormalities have been described in patients with early renal dysfunction (e.g., microalbumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
114
0
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(119 citation statements)
references
References 106 publications
(64 reference statements)
1
114
0
4
Order By: Relevance
“…Furthermore, in CKD patients, cardiovascular disease is the major cause of death, which cannot be entirely explained by the clustering of the traditional cardiovascular risk factors (3). It has been hypothesized that this excessive risk can be attributed, at least in part, to endothelial dysfunction and reduced bioavailability of nitric oxide (NO), which might play a pivotal role in the initiation and progression of atherosclerosis and might be a potential link between cardiovascular disease and CKD (4). In addition, endothelial dysfunction assessed by acetylcholine-stimulated vasodilation has been shown to be associated with the decline of renal function in hypertensive patients (5).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in CKD patients, cardiovascular disease is the major cause of death, which cannot be entirely explained by the clustering of the traditional cardiovascular risk factors (3). It has been hypothesized that this excessive risk can be attributed, at least in part, to endothelial dysfunction and reduced bioavailability of nitric oxide (NO), which might play a pivotal role in the initiation and progression of atherosclerosis and might be a potential link between cardiovascular disease and CKD (4). In addition, endothelial dysfunction assessed by acetylcholine-stimulated vasodilation has been shown to be associated with the decline of renal function in hypertensive patients (5).…”
Section: Introductionmentioning
confidence: 99%
“…A tight relationship between CKD and CVD has become apparent: On the one hand, CKD and its epiphenomena increase the risk for CVD (8); on the other hand, CVD accounts for the majority of morbidity and mortality in patients with CKD (6,9). Diabetes and hypertension are widely acknowledged risk factors for kidney damage, and data increasingly indicate that smoking can have a negative effect on the kidney (for review, see references [10 -12]).…”
mentioning
confidence: 99%
“…atherosclerotic heart disease, 18,19 our present observations suggest that elevation of MCP-1 levels could link to CKD to the increased risk of CVD in a general population. The present study did not clarify how decreased eGFR levels were independently correlated with serum MCP-1 levels.…”
Section: Discussionmentioning
confidence: 51%
“…17 Recent clinical observations have shown that even minor renal dysfunction is associated with the increased risk of future cardiovascular events in a general population. 18,19 Now chronic kidney disease (CKD) is one of the risk factors of cardiovascular disease (CVD) in humans, and the concept of so-called cardiorenal syndrome has received much attention. 20 -22 Although several possible mechanisms that could link to CKD to CVD have been proposed so far, 23,24 given the proatherosclerotic properties of MCP-1, it is conceivable that MCP-1 may contribute to the increased risk of CVD in CKD patients.…”
Section: Introductionmentioning
confidence: 99%